Health Care Services Utilization and Health-Related Quality of Life of Syrian Refugees with Post-Traumatic Stress Symptoms in Germany (the Sanadak Trial) - Grochtdreis T; Röhr S; Jung FU; Nagl M; Renner A; Kersting A; Riedel-Heller SG; König H-H; Dams J (MDPI (Basel, Switzerland), 2021)
Refugees who have fled from the ongoing civil war in Syria that arrived in Germany often develop post-traumatic stress symptoms (PTSS). The aim of this study was to determine health care services utilization (HCSU), health care costs and health-related quality of life (HrQoL) of Syrian refugees with mild to moderate PTSS without current treatment in Germany. The study was based on the baseline sample of a randomized controlled trial of a self-help app for Syrian refugees with PTSS (n = 133). HCSU and HrQoL based on the EQ-5D-5L and its visual analogue scale (EQ-VAS) were assessed with standardized interviews. Annual health care costs were calculated using extrapolated four-month HCSU and standardized unit costs. Associations between health care costs, HrQoL and PTSS severity were examined using generalized linear models. Overall, 85.0% of the sample utilized health care services within four months. The mean total annual health care costs were EUR 1920 per person. PTSS severity was not associated with health care costs. The EQ-5D-5L index score and the EQ-VAS score was 0.82 and 73.6, respectively. For Syrian refugees with higher PTSS severity, the EQ-5D-5L index score was lower (−0.17; p < 0.001). The HCSU and the resulting health care costs of Syrian refugees with mild to moderate PTSS without current treatment are low and those with a higher PTSS severity had a lower HrQoL.
Keywords: Syrian refugees; health care costs; health care services utilization; health-related quality of life; mental health; post-traumatic stress; Facilities and Services Utilization; Germany; Humans; Quality of Life; Refugees; Stress Disorders, Post-Traumatic; Syria